How music works - Byrne, David 1952- (Canongate, 2012)
How Music Works is an unparalleled account of a life in music and an explanation of how and why music works from one of the world's most accomplished performers. With his albums for Talking Heads, his work with Brian Eno or his solo output, David Byrne has been consistently at the forefront of musical - and artistic - innovation. In this extraordinary book Byrne explores why the past matters and what the future might bring. From personal accounts of devising and performing his most famous work, to an exploration of the possibilities of new technologies, Byrne discovers that artistic creation is less about an internal creative spark than we thought and more about external factors such as history, architecture and technology. "The universe of music follows broad and basic evolutionary patterns-as does birdsong, to take one example. It seems the will only triumphs if the context is amenable, just as in Darwinian adaptation. What we hear is determined by what we want to hear, by what can be heard, and by the circumstances that allow it to come into being."